Public speaking workshop - Botley, Simon (Universiti Teknologi MARA, Sarawak, 2004)
29th March 2004 was a special day for a select few Sarawak Campus staff who took part in a public speaking workshop organised in conjunction with UiTM Toastmasters Club. The one-day workshop was given by Dunstan Chan, superstar public speaking expert and communications trainer. Mr. Chan who is a Distinguished Toastmaster as well as a trained lawyer, and interestingly a scuba-diving instructor, put the group through their paces with an exciting series of talks, tutorials and practical exercises.